Gene expression profile analysis of pancreatic cancer based on microarray data - LONG, JIN (Mol Med Rep, 2016)
The present study identified differentially-expressed genes (DEGs) between pancreatic cancer (PC) tissues and normal tissues, and assessed genetic factors associated with the pathogenesis of PC. The mRNA expression microarray dataset, GSE16515, containing 52 samples, including 16 paired tumor and normal tissue samples, and 20 tumor samples, was downloaded from Gene Expression Omnibus. Raw data were normalized and DEGs were identified. Subsequently, clustering was performed, protein-protein interaction networks were drawn, and functional and pathway enrichment analyses of the DEGs were performed. Copy number variations of DEGs were also identified. A total of 1,765 DEGs between PC and normal tissues were identified, including 1,312 upregulated and 453 downregulated DEGs. Upregulated DEGs were associated with the regulation of nucleocytoplasmic and intracellular transport, whereas downregulated DEGs were associated with the response to organic substances and hormone stimulus. The pancreatic cancer pathway was connected to three DEGs, namely transforming growth factor β1 (TGFB1), TGFβ receptor 1 (TGFBR1) and epidermal growth factor (EGF), which had 2, 3 and 5 CNVs, respectively. These results indicated the important roles of TGFB1, TGFBR1 and EGF in the pathogenesis of PC. These genes may be potential therapeutic targets for the treatment of PC.